Interpretation of Short ECGs with a Personal Computer: The Porto Program - Abreu-Lima, C.; Marques de Sá, J. P. (Methods of Information in Medicine, 1990)
A computer program for ECG analysis and interpretation developed at the University of Porto, Portugal is presented. The program runs on a microcomputer and employs the three-lead Frank VCG. The signals are sampled at 250 Hz with 8-bit precision during 5.5 s. Details on signal conditioning and wave recognition and measurement techniques are given. The diagnostic part of the program uses decision-tree logic. The decision rules are mainly derived from the Washington Code. The diagnostic accuracy of four classes (normal, left and right ventricular hypertrophies and myocardial infarction), evaluated in a sample of 1,075 pediatric and adult patients and classified by ECG-independent means was 76%. The program is currently being evaluated on the CSE database.